Electrospun nanofibres in drug delivery: advances in controlled release strategies. Issue 11 (6th March 2023) - Gaydhane, Mrunalini K.; Sharma, Chandra Shekhar; Majumdar, Saptarshi
Abstract : Various approaches to control the release of active molecules or drug molecules through electrospun polymeric nanofibers. Abstract : Emerging drug-delivery systems demand a controlled or programmable or sustained release of drug molecules to improve therapeutic efficacy and patient compliance. Such systems have been heavily investigated as they offer safe, accurate, and quality treatment for numerous diseases. Amongst newly developed drug-delivery systems, electrospun nanofibres have emerged as promising drug excipients and are coming up as promising biomaterials. The inimitable characteristics of electrospun nanofibres in terms of their high surface-to-volume ratio, high porosity, easy drug encapsulation, and programmable release make them an astounding drug-delivery vehicle.